PENGENDALIAN KUALITAS PRODUK TAHU DENGAN PENDEKATAN SIX SIGMA - Moh Ririn Rosyidi; Anik Rufaida (UPN Veteran Jawa Timur, 2022)
Indonesia is still strong and its numbers are not shrinking, especially when the global crisis hits the world. With the existence of Covid-19, it is necessary to be able to control the quality of products so that users can maintain the sales force of products to be marketed. At this time, a virus outbreak called Covid-19 has disturbed economics globally. CV. Sumber Rejeki is located in the Kec. Pangkah, Kab. East Gresik, one of the factories that carries out the processing of tofu making. Tofu made in the industry is white tofu. The process of tofu processing tries to use labor by practicing social distancing during the creation process and some small industrial scale machines. In the creation process at CV. Sumber Rejeki still uses conventional equipment so that quality is very susceptible to disabilities. On March 15, 2020 to April 15, 2020, in the graph, in the 7th treatment there were 23 tofu defects, the opposite was the lowest in the 31st observation which was 6 tofu defects. During the Covid-19 period, using six sigma if the DPMO value was 5,000.00, it was obtained from the CTQ value of 4, the number of products was 300, the number of defective products was 28. The number of known products has a sigma value from the creation of know of 3.88 when covid — 19, while the causative factor is CV. Sumber Rejeki is deemed insufficient or has not fulfilled the needs and satisfaction of consumers, thus it needs revisions to the dominant aspects that cause defects, namely soft texture, dirt, cuts, and holes.